Life, scientific and organizational activities of academician Yefym Fedotovych Lyskun (1873 – 1958) - Prysyazhnyuk, M. V. (History of science and technology, 2016)
In article historical aspects of a vital and scientific way of Ye.F. Lyskun are stated. The scientist’s contribution to development of branch of livestock production and preparation of scientific shots for agrarian economy has been analyzed. The researches on a craniology, cultivation and feeding of farm animals conducted by him, and also technologies of forages are considered.